Analysis of shrinkage and warpage on front panel housing genetic altgorithm (GA) - Muhammad Ezuddin Shafiee (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
In materials processing, Quality and productivity are most important and must be controlled for each product type produced. In an injection moulding process, quality is measured in term of warpage of moulded parts while productivity is qualified on moulding cycle time. In designing moulds for iniection process, achieving to reducing shrinkage and warpage on the part is a huge challenge to mould designers.